The 2011-2019 Media Literacy Improvement: Strategy and Implementation of Sustainable Community Service Program - Dorien Kartikawangi (MITRA: Jurnal Pemberdayaan Masyarakat, 2020)
The importance of public media literacy has been recognized by the School of Communication, Atma Jaya Catholic University of Indonesia for a long time. Various studies that support this issue are then used as a basis for community service program on improving the ability to use media in various places with diverse target audiences. This activity was first carried out by a team of lecturers involving students in 2011 and continued until 2019. There was a fundamental shift in its substance related to the rapid development of information and communication technology. This shift is primarily a form of media. Previously the media used by the public were print, audio, visual and audio visual. With the development of technology and the emergence of digital media, grouping occurs as the old or conventional media and new or digital media. This paper aims to explain the track record of community service in increasing media literacy conducted by the School of Communication, Atma Jaya Catholic University of Indonesia, as a form of evaluation and mapping in an effort to maintain program sustainability. The results of the track record evaluation and mapping show that the shift in the shape of the media requires an adjustment in the substance of the material, namely from increasing the ability to use conventional media, to increasing the ability to use digital media. Therefore, in development, the preparation of materials, delivery methods and implementation, requires the right strategy for this effort to be sustainable. The implementation of the plans arranged shows that collaboration with various parties and an understanding of the culture of the target communities will facilitate the delivery of material and increase the success of the program.